The Ab-initio Study of Bulk Single Layer Defected Graphene Towards Graphene Device - Marriatyi Morsin; Yusmeeraz Yusof (Institute of Advanced Engineering and Science, 2017)
Graphene is a promising new material for the construction of graphene devices because of its surface modification can be tuned the band gap. In this paper, the electronic and transport characteristics of defected graphene device are investigated. Both the electronic and transport characteristics are simulated using density functional theory (DFT). The band structures and transmission spectra are analyzed. The conductance and thermal conductance characteristic for both graphene is compared. From the simulation, it is found that the conductance, thermal conductance, and the I-V curves depend on the transmission spectrum of the graphene sheet or graphene device itself. The comparison between the defected graphene itself shows that the single layer with two vacancies shows better performance.